Women’s Time Allocation in Agricultural Activities in Tehsil Mian Channu, Pakistan: An Economic Analysis - Sheikh, Muhammad Ramzan; Farooq, Fatima; Ali, Hina; Khalid, Sana (iRASD Journal of Economics, 2022)
Women play a significant role in agriculture as they assume various activities in agriculture such as cleaning of fields, fields preparation, sowing, weeding, harvesting, picking, cleaning of grains, drying of grains etc. but, unfortunately, they remain invisible workers. Their participation as decision-makers concerning these activities is also uncertain. This study is an economic analysis of women’s time allocation in agricultural activities in tehsil Mian Channu, Pakistan. A questionnaire is used to collect data from a random sample of 250 female respondents. The study points out the active participation of females in agriculture activities. Age of the woman and education of woman has a negative sign in crop production activities. Age of the woman and education of woman exhibit a positive association with women time allocation in non-crop production activities. Dependency Burdenis positively related to women participation in both crop production activities and non-crop production activities. The results also reveal that the number of adult males in a household is negatively related to woman’s time allocation and a tenant woman allocates more time to crop production activities than non-crop production activities.